Functional Genomics via CRISPR–Cas. Issue 1 (4th January 2019) - Ford, Kyle; McDonald, Daniella; Mali, Prashant
Abstract: RNA-guided CRISPR (clustered regularly interspaced short palindromic repeat)-associated Cas proteins have recently emerged as versatile tools to investigate and engineer the genome. The programmability of CRISPR–Cas has proven especially useful for probing genomic function in high-throughput. Facile single-guide RNA library synthesis allows CRISPR–Cas screening to rapidly investigate the functional consequences of genomic, transcriptomic, and epigenomic perturbations. Furthermore, by combining CRISPR–Cas perturbations with downstream single-cell analyses (flow cytometry, expression profiling, etc.), forward screens can generate robust data sets linking genotypes to complex cellular phenotypes. In the following review, we highlight recent advances in CRISPR–Cas genomic screening while outlining protocols and pitfalls associated with screen implementation. Finally, we describe current challenges limiting the utility of CRISPR–Cas screening as well as future research needed to resolve these impediments. As CRISPR–Cas technologies develop, so too will their clinical applications. Looking ahead, patient centric functional screening in primary cells will likely play a greater role in disease management and therapeutic development. Graphical abstract: Highlights: The programmability of CRISPR–Cas has proven especially useful for probing genomic function in high-throughput. Facile single-guide RNA (sgRNA) library synthesis allows CRISPR–Cas screening to rapidly investigate the functional consequences of genomic, transcriptomic, and epigenomic perturbations. By combining CRISPR–Cas perturbations with downstream single-cell analyses (flow cytometry, expression profiling, etc.), screens can generate robust data sets linking genotypes to complex cellular phenotypes. Highlight recent advances in CRISPR–Cas genomic screening while outlining protocols and pitfalls associated with screen implementation. Describe current challenges limiting the utility of CRISPR–Cas screening as well as future research needed to resolve these impediments.